Arsenic removal in aqueous solutions using FeS2. (15th May 2021) - Fu, Dun; Kurniawan, Tonni Agustiono; Lin, Lan; Li, Yaqiong; Avtar, Ram; Dzarfan Othman, Mohd Hafiz; Li, Feng
Abstract: This study tested the technical feasibility of pyrite and/or persulfate oxidation system for arsenic (As) removal from aqueous solutions. The effects of persulfate on As removal by the pyrite in the integrated treatment were also investigated. Prior to the persulfate addition into the reaction system, the physico-chemical interactions between As and the pyrite alone in aqueous solutions were explored in batch studies. The adsorption mechanisms of As by the adsorbent were also presented. At the same As concentration of 5 mg/L, it was found that As(III) attained a longer equilibrium time (8 h) than As(V) (2 h), while the pyrite worked effectively at pH ranging from 6 to 11. At optimum conditions (0.25 g/L of pyrite, pH 8.0 and 5 mg/L of As(III) concentration), the addition of persulfate (0.5 mM) into the reaction promoted a complete removal of arsenic from the solutions. Consequently, this enabled the treated effluents to meet the arsenic maximum contaminant limit (MCL) of <10  μ g/L according to the World Health Organization (WHO)'s requirements. The redox mechanisms, which involved electron transfer from the S2 2− of the pyrite to Fe 3+, supply Fe 2+ for persulfate decomposition, oxidizing As(III) to As(V). The sulfur species played roles in the redox cycle of the Fe 3+ /Fe 2+ of the pyrite by giving its electrons, while the As(III) oxidation to As(V) was attributed to the pyrite. Overall, this work reveals the applicability of the pyrite as an adsorbent for water treatment and the importance of persulfate addition to promote a complete As removal from aqueous solutions. Graphical abstract: Image 1 Highlights: SO.4 - is the predominant active species at acidic conditions; SO4 . - intensified FeS2 oxidation by yielding iron oxide to co-precipitate arsenic; As(V) sorption capacity of pyrite was higher than that of As(III). Complete As removal was attained by integrated pyrite and persulfate oxidation. Treated effluents met the discharge limit of <10  μ g/L set by the WHO.